Unlocking the power of calcium sulfate: paving the way for periodontal regeneration across time - Mohamad, Ikhwan Hakimi; Nasruddin, Mohd Faiz; Ariffin, Farha (Faculty of Medicine, 2025)
Various bone substitutes—including autograft, allograft, and xenograft—have been used to replace missing bone. However, each has its limitations, prompting interest in alternatives such as alloplastic materials. Calcium sulfate (CS), one of the oldest alloplastic materials, has a long-standing role in regenerative medicine. A primary search using the keywords “alloplastic” and “periodontal regeneration” was performed in PubMed, Cochrane, and Scopus. A secondary search focused on CS, using keywords “calcium sulfate,” “scaffold,” and “periodontal regeneration” in PubMed and Google Scholar. Articles published from 2017 onward were included. A manual search was also conducted to identify relevant studies regardless of publication date. A total of 42 articles were reviewed. Many studies highlight the regenerative potential of CS in periodontal therapy. Compared to xenografts, CS shows better biocompatibility, porosity, and osteoconductivity. It has been used successfully in various applications such as treating intrabony defects, gingival recession, and interproximal bone loss. CS also acts as an effective drug delivery system, especially when combined with tetracycline, and serves as a scaffold for stem cells and periodontal ligament fibroblasts, promoting osteogenic differentiation. CS is a promising alloplastic material in periodontal regeneration. Although it lacks osteoinductive capacity and presents limitations like rapid resorption and low mechanical strength, these can be mitigated by combining it with other biomaterials or using it as a stem cell scaffold. Current evidence supports its potential role in advancing future periodontal regenerative therapies.